Digital technology adoption and farm household income in ethnic minority areas: evidence from Xinjiang, China - Tang, Yan; Tang, Lizhi (Frontiers in Sustainable Food Systems, 2025)
IntroductionPromoting rural income growth and equity remains a critical concern for academia and policymakers. With the rapid development of the digital economy, digital technologies have emerged as key drivers of rural revitalization. However, digital inclusiveness in ethnic minority areas has not received sufficient attention. This topic is not only related to inclusive growth objectives but also directly impacts the progress and benefits of comprehensive rural revitalization.MethodsUsing micro-survey data from Xinjiang in 2023, this study constructs a digital technology adoption index characterized by digital production, digital information processing, and digital marketing. An endogenous switching regression model is employed to address potential selection bias arising from unobservable factors, examining the impact of digital technology adoption on rural household income in ethnic regions and its underlying mechanisms. A quantile treatment effect model is used to capture heterogeneous impacts on income distribution.ResultsDigital technology adoption and its sub-dimensions significantly enhance rural household incomes. The core mechanism lies in strengthening agricultural production and operational capabilities and driving a shift in household livelihood strategies from traditional agriculture-dominated to diversified models. Specifically, digital adoption reduces reliance on traditional labor inputs in agricultural production, boosting agricultural incomes while increasing the likelihood of non-farm employment, thereby promoting income diversification. The income effect of digital adoption varies across income quantiles, with stronger impacts on low-income households than on middle-to-high-income households, contributing to narrowed rural income inequality.DiscussionTo our knowledge, this is the first study focusing on the digitalization process in minority ethnic areas of China. It contributes to understanding the actual progress of digitalization in remote ethnic rural areas, providing theoretical support and practical insights for achieving inclusive growth goals in multi-ethnic regions and formulating differentiated agricultural economic policies.